LIPOMA DISSEMINATUM (AYUSHDHARA, 2015)
A 46-year-old man of medium built was presented with a history of multiple subcutaneous nodules of varying sizes mainly on the back that began to appear since 5 years. It was also found that he is suffering from asymptomatic Hepatitis B since 3 years and was advised to take Liv.52 HB by a local physician. There is no familial history of similar condition. Physical examination revealed that nodules are painless, mobile, soft to touch, with a maximum diameter of 30 cm, most of which were located on the back and an uncommon distribution of lipomas all over the body. Patient’s lipid profile was normal. The case was diagnosed by the modern physicians and advised surgical excision of the lipoma. But the patient was uninterested to undergo the surgical excision. He reported at the OPD of Swami Vivekanand Ayurvedic Panchakarma hospital, Dilshad Garden, New Delhi in the month of Sept 2014.